أثر استخدام التكلفة المستهدفة على قرارات التسعير بالتطبيق على الشركات الصناعية المساهمة العامة المدرجة في بورصة عمان - خالد الحر, عبير; العيسى, محمد سليم (جامعة الوادي - University of Eloued, 2021)
الملخص: تهدف هذه الدارسة إلى بيان أثر استخدام التكلفة المستهدفة على قرارات التسعير،وتم صياغة فرضية رئيسة وستة فرضيات فرعية حول أبعاد التكلفة المستهدفة الستة وهي: (هامش الربح المستهدف، تحليل المنافسين، التركيز على المستهلك، سعر البيع المستهدف، تعاون أعضاء سلسلة القيمة و تصميم وتخطيط المنتج ) على قرارات التسعير، وبعد اجراء المسح الشامل ل (63) شركة صناعية مدرجة في بورصة عمان تعاون مع الباحثين (92%) منها وبواقع (58) شركة. ومن النتائج التي توصلت اليها الدراسة وجود أثر ذو دلالة إحصائية لاستخدام التكلفة المستهدفة وأبعادها الستة على قرارات التسعير وكان العامل الأقوى في التأثير تصميم وتخطيط المنتج وأضعفها هامش الربح المستهدف، ومن أهم التوصيات التي أوصت بها الدراسة القيام بإعداد دراسات مماثلة وتطبيقها على القطاعات الأخرى. Abstract: This study aims to identify the impact of using target costing on pricing decisions with one main hypothesis and six sub-hypotheses were formulated related to six dimensions of target costing which were: (target profit margin, competitor analysis, focus on consumer, target selling price, the collaboration with the value chain members and designing and planning product) on pricing decisions, and after a comprehensive survey of (63) manufacturing companies listed in Amman Stock Exchange, (58) companies that cooperated with the researchers which represented (92%) of total corporations. The main findings were the presence of a significant statistical impact of using the target costing and its six dimensions on pricing decisions, the strongest factor in the effect was designing and planning product and the weakest was target profit margin, and one of the recommendations is to prepare similar studies on other sectors.
مقال
Keywords: محاسبة تكاليف، تكلفة مستهدفة، قرارات تسعير، بورصة عمان; Cost Accounting, Target Costing, Pricing Decisions, Amman Stock Exchange.